2012
DOI: 10.1530/rep-11-0460
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the LH surge on granulosa cell transcript levels as markers of oocyte developmental competence in cattle

Abstract: In the case of in vitro embryonic production, it is known that not all oocytes detain the developmental capacity to form an embryo. This capacity appears to be acquired through completion of folliculogenesis, during which the oocyte and follicular cells influence their respective destinies. The differentiation status of granulosa cells (GCs) could therefore offer an indicator of oocyte quality. The aim of this study was to compare mRNA transcript abundance in GCs associated with oocytes that subsequently reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…However, results of this study suggest that the multiple pre-ovulatory follicles that develop after superstimulation are not typical dominant follicles. The list of upregulated genes in the superstimulation group in this study is similar to those of other studies (Gilbert et al 2011(Gilbert et al , 2012 from dominant follicles before the LH surge at day 14 of the estrous cycle. It is important to note that the granulosa cells from our superstimulation group were collected 24 h after exogenous LH surge (i.e.…”
Section: Hormone Levels In Follicular Fluidsupporting
confidence: 86%
See 2 more Smart Citations
“…However, results of this study suggest that the multiple pre-ovulatory follicles that develop after superstimulation are not typical dominant follicles. The list of upregulated genes in the superstimulation group in this study is similar to those of other studies (Gilbert et al 2011(Gilbert et al , 2012 from dominant follicles before the LH surge at day 14 of the estrous cycle. It is important to note that the granulosa cells from our superstimulation group were collected 24 h after exogenous LH surge (i.e.…”
Section: Hormone Levels In Follicular Fluidsupporting
confidence: 86%
“…In this study, some upregulated genes in the matrix-remodeling network (HPSE, early growth response 1 (EGR1), tissue inhibitor metalloproteinase 1 (TIMP1), and plasminogen activator (PLAT)) are markers of the initiation of ovulatory process (Gilbert et al 2011(Gilbert et al , 2012. HPSE encodes heparanase that cleaves heparan sulfate (one of the tissue glycosaminoglycans) during matrix remodeling and is highly expressed in bovine granulosa cells 12 h after GNRH treatment.…”
Section: The Effect Of Superstimulation On Folliclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The superstimulation protocol used in this study included exogenous administration of FSH over 4 days after follicular wave synchronization and LH 24 h after progesterone-device removal. Therefore, previously documented biomarker genes of early-and late-LH response (those related to vascularization, lipid synthesis, protein localization and intracellular transport) were expected to be already upregulated (Gilbert et al, 2011(Gilbert et al, , 2012Barros et al, 2012). The transcriptomic profile of granulosa cells after superstimulation, however, displayed up-regulation of only a few markers of the LH surge compared to granulosa cells from natural dominant follicles; differentially expressed genes were related to matrix remodeling (i.e., tissue proliferation), disturbance of angiogenesis, apoptosis, and oxidative stress response (Fig.…”
Section: Single Dominant Follicle Versus Many Follicles After Fsh Stimentioning
confidence: 99%
“…22 The coagulation pathway seems to be important in competent follicles according to this study and recent publications from mouse studies 23 and our group have further identified SERPINE1 (Serpin peptidase inhibitor, clade E (nexin, plasminogen activator inhibitor type 1), member 1), SERPINA5 (serpin peptidase inhibitor, clade A [alpha-1 antiproteinase, antitrypsin], member 5), F3 (coagulation factor III (thromboplastin, tissue factor), A2M (alpha-2-macroglobulin), PLAUR (plasminogen activator, urokinase receptor), and F2R (coagulation factor II [thrombin] receptor) as a determinant of oocyte quality. 24,25 Gene selection. In this study, genes with high fold change values, interesting positions in pathways, and good genetic opportunities (availabilities of SNPs and their MAFs) were selected.…”
mentioning
confidence: 99%